A Review of Current Management of Vitreomacular Traction and Macular Hole - Alfredo García-Layana; José García-Arumí; José M. Ruiz-Moreno; Lluís Arias-Barquet; Francisco Cabrera-López; Marta S. Figueroa (Journal of Ophthalmology)
The paper presents a review of the sequence of events of posterior vitreous detachment (PVD), vitreomacular adhesion (VMA), vitreomacular traction (VMT), and macular hole (MH) from their pathophysiological aspects, clinical features, diagnostic implications, and current management strategies. A treatment algorithm to be used in clinical practice in patients with VMA, VMT, and MH based on the presence of symptoms, visual acuity, associated epiretinal membrane, and width of the vitreous attachment is presented. Observation, pharmacologic vitreolysis with ocriplasmin, and surgical treatment are positioned as treatment options in the different steps of the therapeutic algorithm, with clear indications of the paths to be followed according to the initial presenting manifestations and the patient’s clinical course.